2D study of AlGaN/AlN/GaN/AlGaN HEMTs' response to traps. (February 2019) - Hezabra, A.; Abdeslam, N. A.; Sengouga, N.; Yagoub, M. C. E.
Abstract: In this work, the effects of GaN channel traps and temperature on the performance of AlGaN/AlN/GaN/AlGaN high electron mobility transistors (HEMTs) on Si (111) substrate, were investigated. 2D simulations carried out using the Silvaco TCAD simulator tool for different drain and gate voltages showed that acceptor-like traps in the channel have a significant influence on the DC and RF characteristics. It was found that deeper acceptors below the conduction band with larger concentration have a more pronounced effect on the transistor performance. Meanwhile, the donor-like traps show no influence. Pulsing the device with different pulse widths and bias conditions, as well as increasing temperature, showed that the traps are more ionized when the pulse is wider or the temperature is higher, which can degrade the drain current and thus the DC characteristics of the transistor. Passivation of the transistor has also a beneficial effect on performance.